Predictors of mortality in patients with COVID-19 by flow cytometry - Marco Bonilla Izquierdo; Ana María Navas Romo; Aurora Gema Sicilia Zafra; Juan de Dios López-González Garrido (Clinical Immunology Communications, 2023)
Despite the great impact of severe acute respiratory syndrome caused by coronavirus 2 (SARS-CoV-2), we still lack techniques that allow us to anticipate the natural history of the disease in order to avoid or shorten the clinical period of the disease. The values of nine cytokines were measured in COVID-19+ patients admitted to the Hospital Universitario Reina Sofía (HURS) using flow cytometry. The cytokines measured are IL-1ß, IL-6, MCP-1, IP-10, IL-10, IL-8, IL-12, IFN-γ and TNF-α. Given the absence of previous studies on cytokine values in healthy patients using the flow cytometry technique, and the low availability of resources in the first waves of COVID-19, a control group was lacking, all resources were employed for monitoring sick patients. However, this study has revealed a greater increase in two specific cytokines, which are also found to be higher than the rest in healthy patients: MCP-1 and IP-10, which are mainly responsible for cytokine storm and post-disease thrombosis.